Multi-instrument analysis of far-ultraviolet aurora in the southern hemisphere of Comet 67P/Churyumov-Gerasimenko - Stephenson,P; Galand,M; Feldman,PD; Beth,A; Rubin,M; Bockelée-Morvan,D; Biver,N; -C,Cheng Y; Parker,J; Burch,J; Johansson,FL; Eriksson,A (Astronomy and Astrophysics: a European journal, 2021)
Aims. We aim to determine whether dissociative excitation of cometary neutrals by electron impact is the major source of far ultraviolet (FUV) emissions at comet 67P/Churyumov-Gerasimenko in the southern hemisphere at large heliocentric distances, bothduring quiet conditions and impacts of corotating interaction regions observed in the summer of 2016.Methods. We combined multiple datasets from the Rosetta mission through a multi-instrument analysis to complete the first forwardmodelling of FUV emissions in the southern hemisphere of comet 67P and compared modelled brightnesses to observations with theAlice FUV imaging spectrograph. We modelled the brightness of OI1356, OI1304, Lyman-β, CI1657, and CII1335 emissions, whichare associated with the dissociation products of the four major neutral species in the coma: CO2, H2O, CO, and O2. The suprathermalelectron population was probed by the Ion and Electron Sensor of the Rosetta Plasma Consortium (RPC/IES) and the neutral col umn density was constrained by several instruments: the Rosetta Orbiter Spectrometer for Ion and Neutral Analysis (ROSINA), theMicrowave Instrument for the Rosetta Orbiter (MIRO) and the Visual InfraRed Thermal Imaging Spectrometer (VIRTIS).Results. The modelled and observed brightnesses of the FUV emission lines agree closely when viewing nadir and dissociativeexcitation by electron impact is shown to be the dominant source of emissions away from perihelion. The CII1335 emissions areshown to be consistent with the volume mixing ratio of CO derived from ROSINA. When viewing the limb during the impactsof corotating interaction regions, the model reproduces brightnesses of OI1356 and CI1657 well, but resonance scattering in theextended coma may contribute significantly to the observed Lyman-β and OI1304 emissions. The correlation between variationsin the suprathermal electron flux and the observed FUV line brightnesses when viewing the comet’s limb suggests electrons areaccelerated on